2015
DOI: 10.3402/meo.v20.27840
|View full text |Cite
|
Sign up to set email alerts
|

Stress and burnout among critical care fellows: preliminary evaluation of an educational intervention

Abstract: BackgroundDespite a demanding work environment, information on stress and burnout of critical care fellows is limited.ObjectivesTo assess 1) levels of burnout, perceived stress, and quality of life in critical care fellows, and 2) the impact of a brief stress management training on these outcomes.MethodsIn a tertiary care academic medical center, 58 critical care fellows of varying subspecialties and training levels were surveyed to assess baseline levels of stress and burnout. Twenty-one of the 58 critical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…22 Brief training is desirable, but studies have shown mixed effects of brief mind-body training on burnout, stress, and empathy. 23 29…”
mentioning
confidence: 99%
“…22 Brief training is desirable, but studies have shown mixed effects of brief mind-body training on burnout, stress, and empathy. 23 29…”
mentioning
confidence: 99%
“…19 , 23 , 4547 To our knowledge, this study is the first of its kind by focusing on an intervention for ICU providers who have been found to have high burnout. 48 There is evidence that those with higher critical positivity ratios have more flexibility and resiliency to adversity, more social resources, and improved well-being 31 and potentially less burnout. We believe our findings of improving the critical positivity ratio are both statistically and clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…107 Critical care fellow participants in a SMART program intervention felt the training provided them with tools to apply during stressful situations, but did not demonstrate improved burnout scores. 108 Similarly, Maher found that a departmentally-instituted educational program designed to improve surgical resident performance during stressful scenarios showed a trend toward improved performance scoring but no difference in anxiety levels. However, 91% of residents rated the stress training as valuable.…”
Section: Parsons Et Almentioning
confidence: 98%
“…However, 91% of residents rated the stress training as valuable. [108][109] While residents and fellows consistently report subjective benefit from resiliency training, improvement in burnout scores have not been reliably demonstrated. Resiliency training is not the only intervention that has failed to show an improvement in burnout scores.…”
Section: Parsons Et Almentioning
confidence: 99%